Predicting the Effective Elastic Properties of Polymer Bonded Explosives based on Micromechanical Methods. Issue 2 (3rd April 2018) - Wang, Jingcheng; Luo, Jingrun
ABSTRACT: Due to the extremely high particle volume fraction (greater than 85%) and damage feature of polymer bonded explosives (PBXs), conventional micromechanical methods lead to inaccurate estimates on their effective elastic properties. According to their manufacture characteristics, a multistep approach based on micromechanical methods is proposed. PBXs are treated as pseudo poly-crystal materials consisting of equivalent composite particles (explosive crystals with binder coating), rather than two-phase composites composed of explosive particles and binder matrix. Moduli of composite spheres are obtained by generalized self-consistent method first, and the self-consistent method is modified to calculate the effective moduli of PBX. Defects and particle size distribution are considered by Mori-Tanaka method. Results show that when the multistep approach is applied to PBX 9501, estimates are far more accurate than the conventional micromechanical results. The bulk modulus is 5.75% higher, and shear modulus is 5.78% lower than the experimental values. Further analyses discover that while particle volume fraction and the binder's property have significant influences on the effective moduli of PBX, the moduli of particles present minor influences. Investigation of another particle size distribution indicates that the use of more fine particles will enhance the effective moduli of PBX.